Recovery of the protein fraction with high antioxidant activity from red seaweed industrial solid residue after agar extraction by subcritical water treatment - Trigueros, Ester; Sanz, M. Teresa; Alonso-Riaño, Patricia; Beltrán, Sagrario; Ramos, Cipriano; Melgosa, Rodrigo (Journal of applied phycology, 2021)
In this work valorization of the underexploited industrial solid residue generated after agar extraction from Gelidium sesquipedale was studied by using subcritical water in a semicontinuous fix-bed reactor. First, a complete characterization of this by-product was carried out, determining up to 21% (w/w) of protein content (for a nitrogen factor of 4.9) with high content of essential amino acids, 37% (w/w) of carbohydrate fraction and high amount of ash, 22% (w/w). The effect of temperature, in the range from 129 to 200 °C, and flow rate, in the range from 2 to 6 mL min −1 , on protein and carbon fraction extraction/hydrolysis was studied. At constant flow rate of 2 mL min −1 , a maximum in the protein extraction was achieved at 185 °C. Higher temperatures led to degradation of protein or its hydrolysis products. Free amino acids release followed the same trend as the protein fraction. The most temperature sensitive amino acids, as determined by gas chromatography (EZ:faast Phenomenex), were serine and aspartic and glutamic acids. As a consequence, the selectivity towards non-polar amino acids increased by working at high severity factors. A Pearson correlation between antioxidant capacity of the collected extracts with the bioactive compounds determined in the extracts (total polyphenolic compounds –TPC-, peptides and free amino acids) was established, being stronger for TPC. The ash content in the solid residue after treatment steadily increased with temperature due to non-solubilization being possible its application in agriculture as fertilizers.